BILL NO. HB 19 AMENDMENT NO. (FOR DRAFTERS USE ONLY) SENATE ACTION HOUSE ACTION (Tufts Archival Research Center, 2007)
Amendment to bill H.B. 19 prohibiting any person from advertising or promoting an alcoholic beverage or smoking product. Mentions that all money received from fines, will go to the Addictions Education Trust Fund where the money will be used for anti-smoking/drinking campaigns in Public Schools.